Analisis Dampak Dominasi Pengusaha Tambang Dan Minyak Dalam Lembaga Legislatif Nasional Terhadap Pemanfaatan Energi Baru Terbarukan - Taufik Noor Isya; Tri Susilowati (Universitas Sains dan Teknologi Komputer, 2023)
Elections are an important moment in the implementation of the democratic system in Indonesia, as a form of freedom for the people to express their aspirations in choosing representatives who will sit in parliament. The large costs that must be incurred in participating in the election process, in this case, of course have a lasting impact on reviewing the involvement of third parties or the dominance of entrepreneurs in entering parliament. The inclusion of entrepreneurs in parliament can of course have a big impact on the national system, especially in the aspect of utilization and development of new renewable energy. This research was then analyzed conceptually sociologically, which attempted to analyze the extent to which the conception of legal science plays a role in social society and carries out its function optimally. The results of this research are that the involvement of entrepreneurs in running as legislative candidates must of course be limited through term limits.